Professor coordenador na formação contínua de professores: um estudo em escolas do município de Limeira - Antunes, Luciana Estessi Bento [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research consisted of a qualitative research in education, with collections of data held in the academic year of 2013, with nine educational coordinators from six different schools in the city of Limeira, in the spaces of HTPCs (schedules Pedagogical Work Collective). The focus of this research is the analysis of the contribution of the role of coordinators in the continuing education of teachers, and the HTPC as a privileged space for it. Given this premise, it was necessary to investigate the dynamics of professional Pedagogical Coordinator in the school context, ie with the management team and teachers, analyzing the routine working in this professional organization of HTPCs and the Action Plan of Work Coordinators teaching. As a theoretical contribution, that embased in Alarcão (2008), Nóvoa (1992), Placco (2003), Vasconcellos (2006), among others. This study uses the method of content analysis to the data collected through a qualitative approach, using semi-structured interviews, documentary review of the Work Plan and Action Plan Coordinators and observations in HTPCs. This study enabled the greater understanding that teacher education is an inherent part of the pedagogical coordinator within the school routine, that does not finish with the initial formation process; rather, imposes itself as an indispensable training continues so that professional practices become the basis for training. Another relevant aspect is the idea that HTPCs are becoming spaces / training places, which enable the exchange of experiences of knowledge that contribute to the professional development throughout their careers in order to contribute to the formation of professional identity. As a conclusion it is pertinent to point out that the formative processes of teachers should assume the character of a fresh start, renewal, innovation, personal and professional reality, making the practice of pedagogical coordinator a key element in mediating the...

A presente pesquisa se compôs de uma investigação qualitativa em Educação, com coletas de dados realizada no ano letivo de 2013, com nove Professores Coordenadores de seis escolas diferentes do Município de Limeira, nos espaços de HTPCs (Horários de Trabalho Pedagógico Coletivo). O foco dessa investigação está na análise da contribuição do papel dos professores coordenadores na formação continuada dos professores, tendo o HTPC como um espaço privilegiado para isso. Em função dessa premissa, foi necessário investigarmos a dinâmica profissional do professor coordenador, no contexto escolar, isto é, junto à equipe gestora e aos professores, analisando a rotina de trabalho deste profissional na organização dos HTPCs e o Plano de Ação de Trabalho dos Professores Coodernadores. Como aporte teórico, embasou-se em Alarcão (2008), Nóvoa (1992), Placco (2003), Vasconcellos (2006), entre outros. Esse estudo utiliza o método de análise de conteúdo para os dados coletados, através de uma abordagem qualitativa, utilizando entrevistas semiestruturadas, analise documental do Plano de Trabalho e Plano de Ação dos coordenadores e observações nos HTPCs. Esse estudo possibilitou o maior entendimento de que a formação do professor é um processo inerente ao papel do professor coordenador no espaço do cotidiano escolar, que não se finaliza com a formação inicial; ao contrário, impõe-se como indispensável à formação continua, para que práticas profissionais se tornem a base da formação. Outro aspecto relevante é a ideia de que as HTPCs devem se tornar espaços/lugares formativos, que possibilitam a troca de experiências de saberes que contribuam para o desenvolvimento profissional durante toda a carreira, de modo a contribuir para a constituição da identidade profissional. Como conclusão é pertinente apontarmos que os processos formativos dos professores devem assumir um caráter de recomeço, renovação...
Keywords: Teachers, Training of; Professores - Formação; Orientadores educacionais; Escolas - Organização e administração - Limeira (SP); Horário de trabalho pedagógico coletivo